Automatic Generation of School Activities for Teaching English to Children - Lucena, Lorenna Marinho; Santos, Matheus Lisboa Oliveira dos; Campelo, Claudio E. C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
Activity sheets are essential tools for developing basic skills, integrating theoretical and practical knowledge. For children, they should be playful, creative and interactive, facilitating the association of ideas. Creating these sheets is a challenge, requiring technical and pedagogical skills, especially in language teaching. This article proposes the use of Large Language Models (LLMs) with fine-tuning to generate English as a Second Language (ESL) exercises for children. Different models were evaluated and compared against fine-tuned GPT-3.5. The approach was evaluated with the help of ESL teaching experts, based on criteria such as naturalness, usefulness, diversity and personalization. The results indicated that the fine-tuning approach is promising.